História do povoamento de Picote (HISTPP) : projeto de investigação (2012-2015) - Centeno, Rui; Barroca, Mário Jorge; Ferreira, Daniela de Freitas; Monteiro-Rodrigues, Sérgio; Morais, Rui; Sanches, Maria de Jesus; Soeiro, Teresa; Vaz, Filipe Costa (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
In a time of great decline of public funding in archaeological investigation, it was formed in 2012 the research project “História do Povoamento de Picote”, proposed by Associação para o Desenvolvimento Integrado de Picote (Frauga) to the University of Porto (UP). This project was created with the main objective of carrying out excavations in the archaeological site of Puio, as well as the recovery of other information’s regarding the past human settlement of Picote village